Progressive deafness–dystonia due to SERAC1 mutations: A study of 67 cases. Issue 6 (20th December 2017) - Maas, Roeltje R.; Iwanicka‐Pronicka, Katarzyna; Kalkan Ucar, Sema; Alhaddad, Bader; AlSayed, Moeenaldeen; Al‐Owain, Mohammed A.; Al‐Zaidan, Hamad I.; Balasubramaniam, Shanti; Barić, Ivo; Bubshait, Dalal K.; Burlina, Alberto; Christodoulou, John; et al.
Abstract : Objective: 3‐Methylglutaconic aciduria, dystonia–deafness, hepatopathy, encephalopathy, Leigh‐like syndrome (MEGDHEL) syndrome is caused by biallelic variants in SERAC1 . Methods: This multicenter study addressed the course of disease for each organ system. Metabolic, neuroradiological, and genetic findings are reported. Results: Sixty‐seven individuals (39 previously unreported) from 59 families were included (age range = 5 days–33.4 years, median age = 9 years). A total of 41 different SERAC1 variants were identified, including 20 that have not been reported before. With the exception of 2 families with a milder phenotype, all affected individuals showed a strikingly homogeneous phenotype and time course. Severe, reversible neonatal liver dysfunction and hypoglycemia were seen in >40% of all cases. Starting at a median age of 6 months, muscular hypotonia (91%) was seen, followed by progressive spasticity (82%, median onset = 15 months) and dystonia (82%, 18 months). The majority of affected individuals never learned to walk (68%). Seventy‐nine percent suffered hearing loss, 58% never learned to speak, and nearly all had significant intellectual disability (88%). Magnetic resonance imaging features were accordingly homogenous, with bilateral basal ganglia involvement (98%); the characteristic "putaminal eye" was seen in 53%. The urinary marker 3‐methylglutaconic aciduria was present in virtually all patients (98%). Supportive treatment focused on spasticity and drooling, and was effective in the individuals treated; hearing aids or cochlear implants did not improve communication skills. Interpretation: MEGDHEL syndrome is a progressive deafness–dystonia syndrome with frequent and reversible neonatal liver involvement and a strikingly homogenous course of disease. Ann Neurol 2017;82:1004–1015